1981
DOI: 10.1002/eji.1830110505
|View full text |Cite
|
Sign up to set email alerts
|

Agents which block membrane lipid peroxidation enhance mouse spleen cell immune activities in vitro: relationship to the enhancing activity of 2‐mercaptoethanol

Abstract: A broad spectrum of agents known to block various steps in the lipid peroxidation process were tested for their ability to protect mouse spleen cells and thereby enhance their activities, in vitro, in either the primary antibody response or the lipopolysaccharide-stimulated proliferation response. Each agent (superoxide dismutase, butylated hydroxyanisole/butylated hydroxytoluene/n-propyl gallate, lucigenin, and alpha-tocopherol) was able to enhance the cellular response in both assay systems. The degree of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…2-Mercaptoethanol (2-ME) is usually added to the culture medium for in vitro lymphocyte proliferation assay, as a synthetic antioxidant agent to enhance the (cellular) response (27,28). This enhancement was mediated by the enhanced availability of glutathione to prevent cell membrane lipid peroxidation (29). Oonishi et al found that, in the presence of 2-ME, there was no enhancement of proliferation by a-tocopherol (30).…”
Section: Discussionmentioning
confidence: 99%
“…2-Mercaptoethanol (2-ME) is usually added to the culture medium for in vitro lymphocyte proliferation assay, as a synthetic antioxidant agent to enhance the (cellular) response (27,28). This enhancement was mediated by the enhanced availability of glutathione to prevent cell membrane lipid peroxidation (29). Oonishi et al found that, in the presence of 2-ME, there was no enhancement of proliferation by a-tocopherol (30).…”
Section: Discussionmentioning
confidence: 99%
“…Early investigations of the mechanism of action of 2-ME emphasized its antioxidant properties (Toohey, 1975;Hoffeld, 1981). However, the observation that the oxidized (disulfide) form of 2-ME could be as effective as the reduced form (Ohmori and Yamamoto, 1983) indicated that direct antioxidant actions alone could not explain the effect of 2-ME on cultured lymphocytes.…”
mentioning
confidence: 97%
“…We added transferrin, as suggested by Iscove and Melchers (1978), and reduced GSH, whose high content in foetal calf serum (FCS) accounts for its usefulness in murine cell cultures (Hoffeld & Oppenheim, 1980) and whose promoting activity on human PBL proliferation has been recently demonstrated (Hoffeld, 1981;Noelle & Lawrence, 1981). GSH, together with 2-ME, which prevents its spontaneous oxidation, allowed us to eliminate FCS and avoid the use of a special low oxygen-tension mixture in the incubation chamber.…”
Section: Lymphocyte Culturesmentioning
confidence: 99%